Web: Sistemas sobrecargados: Leyes de drogas y cárceles de América Latina (Revista Policía y Seguridad Pública, 2014)
DOI: http://dx.doi.org/10.5377/rpsp.v3i1.1344Revista Policía y Seguridad Pública 3(1) 2013: 367-368